2D AlB2 flakes for epitaxial thin film growth. Issue 16 (21st June 2018) - Humood, Mohammad; Meyer, Jacob L.; Verkhoturov, Stanislav V.; Ozkan, Tanil; Eller, Michael; Schweikert, Emile A.; Economy, James; Polycarpou, Andreas A.
Abstract: Abstract : In this study, we report on the mechanical cleavage of conductive metal-based aluminum diboride (AlB2 ) flakes. The cleavage resulted in a highly single crystalline 2D material and had an atomically flat and smooth surface as shown by atomic force microscopy (AFM) and secondary ion mass spectrometry. Nanoindentation and AFM imaging of freshly cleaved specimens revealed sub-nm roughness and 30% improvement in the nanomechanical properties as compared to the as-grown AlB2 flakes. Once exposed to ambient air, the cleaved AlB2 flakes formed a superficial oxidation layer of less than 1 nm thickness within 5 min. Owing to the smooth surface, ultra-thin and stable oxide layer, and the excellent mechanical and electrical characteristics of AlB2, the cleaved flakes present an ideal 2D material for emerging applications in microfabrication such as the growth of epitaxial thin films. To prove the sub-nm surface characteristics of cleaved AlB2, a 10-nm thick TiO2 film was deposited on a freshly cleaved AlB2 using atomic layer deposition. Surface roughness and compositional consistency of this film were compared with a control sample deposited on Si. The TiO2 film on AlB2 showed a distinct thin interface layer with fewer defects than TiO2 on Si and superior flatness.